Inhibition of neoplastic development in the liver by hepatocyte growth factor in a transgenic mouse model. - Santoni-Rugiu, E (1996)
Overexpression of the c-myc oncogene is associated with a variety of both human and experimental tumors, and cooperation of other oncogenes and growth factors with the myc family are critical in the evolution of the malignant phenotype. The interaction of hepatocyte growth factor (HGF) with c-myc during hepatocarcinogenesis in a transgenic mouse model has been analyzed. While sustained overexpression of c-myc in the liver leads to cancer, coexpression of HGF and c-myc in the liver delayed the appearance of preneoplastic lesions and prevented malignant conversion. Furthermore, tumor promotion by phenobarbital was completely inhibited in the c-myc/HGF double transgenic mice, whereas phenobarbital was an effective tumor promoter in the c-myc single transgenic mice. The results indicate that HGF may function as a tumor suppressor during early stages of liver carcinogenesis, and suggest the possibility of therapeutic application for this cytokine.